Analisis Sistem Informasi Manajemen Rumah Sakit Di Rumah Sakit Gigi Dan Mulut Ugm Prof. Soedomo Sleman Daerah Istimewa Yogyakarta - NAJIB, KHOIRI (Jurnal Bisnis Administrasi dan Manajemen, 2025)
In order to obtain a clearer analysis and specifications, researchersuse the PIECES (Performance, Information, Economy, Control,Efficiency, and Service) framework analysis. This analysis isexpected to help in the development of Management InformationSystems at Rumah Sakit Gigi dan Mulut UGM Prof. Soedomo. ThisSystem Performance is carried out to determine the performance ofa system whether it is running well or not. Performance can bemeasured by the amount of production and the time used to customizethe work. Based on information, it has provided informationaccording to the needs that have accuracy with an average of 85%.Economic as measured by reusability and resources that it iseffective and efficient in the use of available time resources withavailable manpower. economic analysis of SIMRS as measured byreusability and resources that it is effective and efficient in the use ofavailable time resources with available manpower. Control is verysafe, because it uses usernames and passwords as needed so thatother people cannot access, units that are not their responsibility.Efficiency, has been used properly and maximally, both in enteringdata and in processing data. Services of SIMRS can provideconvenience for users in the hospital.